Township theatre-making as a developmental tool for Khayelitsha youth : an applied theatre study from an ethnographic perspective - Mbele, Ongezwa (Department of Drama, 2015)
This dissertation examines the theatre making process of a youth theatre group in Khayelitsha called Qina n Divas. It considers why and how this theatre making process is a youth development tool within the ambit of applied theatre. The study is partly driven by my memories and experiences of growing up in a township, as well as applied theatre aims, which are to use theatre to address social issues and honor the participants’ ways of using theatre to address their issues. I examine how the Qina n Divas young people, who are growing up in an environment that challenges their development, use theatre making as a way of reviewing and revaluing their lives. I identify and examine the various systems that influence the youth’s lives and that limit their use of theatre as a liberation tool in that the theatre making is a rehearsal of their issues rather than becoming a means of interrogating the issues. As I am immersed in the township context I also reflect on my involvement and how I unintentionally became part of the problem, which limits the youth’s development. My position of being an applied theatre practitioner and researcher is informed by my Xhosa cultural identity, my Zulu schooling and my English-speaking higher education, which also influenced my relationship with the youth. In the research process, the young people and I exchanged several theatre making methods. The theatre making explored themes of bullying, rape, environmental issues, parental love and abandonment, which revealed the youth’s emotions and thoughts about these themes. In spite of the above-mentioned limitations, I propose that theatre making allows the youth to use their imaginations to construct their identity in a partly secure space and to journey beyond the township to the Cape Town suburbs. The theatre practice induces a sense of hope amongst the youth and allows them to voice the issues that matter to them.